MULTIPLE KNOWLEDGE NETWORKS AND INNOVATIVE BEHAVIOR: A STUDY IN INDONESIA’S TOP DIGITAL START-UP COMPANIES - Hardja, Stella; Sunardi, Oki; Widyarini, Maria (Jurnal Manajemen Teknologi, 2020)
Abstract. Knowledge and innovation have become critical aspects of gaining competitive advantage and success in organizations. This study aims to uncover the role of multiple knowledge networks in the formation of innovative behavior and its relationship with supply chain collaboration in Indonesian startup companies. The survey involved 100 employees from the top five Indonesian digital startup companies as respondents. Model testing utilized SEM PLS, followed by triangulation through semi-structured interviews. The result showed that multiple knowledge networks and supply chain collaboration were positively related to innovative behavior. However, the work culture in Indonesian startups was somehow low in terms of exchanging knowledge and information. The lack of collaboration between the actors of the supply chain network has caused the knowledge network not to form correctly in Indonesian startup companies.Keywords: Multiple knowledge networks, supply chain collaboration, innovative behavior, startups, IndonesiaAbstrak. Pengetahuan dan inovasi merupakan aspek-aspek penting dalam membentuk keunggulan kompetitif dan keberhasilan perusahaan. Penelitian ini bertujuan untuk memahami lebih dalam mengenai peran multiple knowledge networks terhadap pembentukan perilaku inovatif serta hubungannya dengan kolaborasi rantai pasok di perusahaan startup Indonesia. Survei dilakukan kepada 100 karyawan dari lima perusahaan startup terbesar di Indonesia sebagai responden. Uji model dilakukan dengan menggunakan SEM PLS, dilanjutkan dengan triangulasi melalui wawancara semi terstruktur. Penelitian ini menunjukkan bahwa multiple knowledge networks dan kolaborasi rantai pasok berhubungan positif terhadap perilaku inovatif. Namun demikian, budaya kerja di perusahaan startup Indonesia tergolong masih rendah dalam hal bertukar pengetahuan dan informasi. Rendahnya kolaborasi antar actor dalam jaringan rantai pasok turut berperan tidak terbentuknya jaringan pengetahuan yang baik di perusahaan startup Indonesia.Kata kunci: Multiple knowledge networks, kolaborasi rantai pasok, perilaku inovatif, startups, Indonesia